Perancangan Set Furnitur Sebagai Fasilitas Belajar, Bersantai, dan Penyimpanan untuk Anak Usia 3-5 Tahun Dalam Rumah Tinggal - Claudia Limantara (Intra, 2017)
Residential houses are the first place and facilities where children try to learn about new things. The necessity of learning, relaxing, and keeping facilities becomes one of the necessities of furniture that must be facilitated for children with the age range of 3-5 years (golden age). The role and function of the furniture became easier to understand which is used in residential houses. Combining kid’s activities into 3 different types of furniture, geometric shapes, primer colors, and constructions chosen for the steps of the furniture. Kiddos itself being chosen as the theme which means furniture that kids like de most, everything about kids combined to make the suitable and right furniture. This design is expected to necessity the needs of children's activities in space and the resulting design can support the creative process and development of children.